2019
DOI: 10.1002/1873-3468.13456
|View full text |Cite
|
Sign up to set email alerts
|

HIC2, a new transcription activator of SIRT1

Abstract: The protein deacetylase SIRT1 is crucial to numerous physiological processes, such as aging, metabolism, and autoimmunity, and is repressed by various transcription factors, including HIC1. Conversely, we found that HIC2, which is highly homologous to HIC1, is a transcriptional activator of SIRT1 due to opposite activity of the intermediate domains of the two homologs. Importantly, this relationship between HIC2 and SIRT1 could be important for cardiac development, where both proteins are implicated. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…HIC2 was found to be a pivotal transcriptional activator of SIRT1 and consequently upregulates SIRT1 in the heart and potentially many other SIRT‐regulated physiological processes, which might protect the heart from I/R injury 19 . However, further experimental data found that HIC2 acts as a tumor suppressor gene and transcription repressor in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…HIC2 was found to be a pivotal transcriptional activator of SIRT1 and consequently upregulates SIRT1 in the heart and potentially many other SIRT‐regulated physiological processes, which might protect the heart from I/R injury 19 . However, further experimental data found that HIC2 acts as a tumor suppressor gene and transcription repressor in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of HIC1 function promoted tumorigenesis by derepressing SIRT1 and thereby attenuated p53 function by deacetylation, which increases cancer risk in mammals 14 . Recently, we found that HIC2, a homolog to HIC1 with differing intermediate domains, is a transcriptional activator of SIRT1 and may protect the heart from ischemia/reperfusion (I/R) injury 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The promoter-reporter fusion construct pGL2- SIRT1 -Luc and the expression vectors pcDNA3-FLAG- Zbtb7c , pcDNA3.1- Zbtb7c , pcDNA3- p53 , pcDNA3.1- HIC-1 , and pCMV- LacZ , in various combinations were transiently transfected into cells using Lipofectamine Plus reagent (Invitrogen, CA) and analyzed as described elsewhere 15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIC family members include HIC1 and HIC2, with HIC2 the most greatly expressed in beta-cells (Extended Data Figure 8b). Interestingly, HIC2 is a transactivator of SIRT1 47 and the loss of SIRT1 impairs glucose sensing in beta-cells in mice 48 . Tier 2 disrupted motif families include TEAD and SMAD (Extended Data Figure 8c).…”
Section: Motif Analysismentioning
confidence: 99%